Structural influence of chromium substituted magnetite ferrofluids on the optical and antibacterial characteristics. (March 2023) - Babukutty, Blessy; Ponnamma, Deepalekshmi; Nair, Swapna S.; Jose, Jiya; Bhat, Saritha G.; Thomas, Sabu
Abstract: A series of chromium substituted magnetite (Crx Fe1−x Fe2 O4 ) ferrofluids with various concentrations ranging from x = 0–0.8 is reported in this work. Simple, cost effective and gentle co-precipitation method is followed for the synthesis, involving the stabilization by tetramethylammoniumhydroxide (TMOAH). Ultrafine nanoparticles of magnetite ferrofluids with good homogeneity exhibit promising structural, optical and magnetic, characteristics. The optimization and control of magnetic grain size during the co-precipitation reaction by regulating the experimental conditions (temperature and pH) ensures the formation of least possible grains. In addition, the grain growth is restricted by the surfactant (TMOAH) by in situ capping. The well optimized crystalline structure of the magnetic nanoparticles influence the morphological features, optical band gap, saturation magnetization, magnetic coercivity and remanence. As the composition of Cr increases from x = 0.2 to x = 0.8, the crystalline size decreases reaching a minimum value of 9 nm. At the same time, the magnetic moment also becomes 1.3 ± 0.08 at a saturation point of 33 ± 0.13 emu/g at the highest Cr composition. For all compositions, the optical band gaps vary within 1.35–2.3 eV range. The antibacterial activity of chromium-substituted ferrofluids against Escherischia coli and Staphylococcus aureus is highlighted in this study. The high content of chromium ions (x = 0–0.8) in the magnetite ferrofluids coupled with the smaller particle sizes generate strong anti-microbial activity for the particles and thereby find application in medical field. Graphical Abstract: ga1